Eremulus flagellifer Berlese 1908 - Murvanidze, Maka; Cilbircioğlu, Cihan; Özdemir, Esengül; Inak, Emre (Zenodo, 2020)
Published as part of Murvanidze, Maka, Cilbircioğlu, Cihan, Özdemir, Esengül & Inak, Emre, 2020, Checklist of oribatid mites (Acari: Oribatida) of the Central Black Sea basin of Turkey with new records for the country, pp. 255-277 in Persian Journal of Acarology 9 (3) on page 259, DOI: 10.22073/pja.v9i3.61909, http://zenodo.org/record/5236444

Eremulus flagellifer Berlese, 1908 Material – One specimen in Daday forest, N 41° 23′ 55.18′′, E 33° 13′ 09.44′′, alt. = 1136 m, 19 October 2018, tree bark and debris from P. nigra . Prevous record in Turkey – Yozgat Province (Per et al. 2018). Global distribution – Cosmopolitan. Ecology – Forest soils and meadows.
Keywords: Arthropoda; Arachnida; Animalia; Biodiversity; Sarcoptiformes; Eremulus; Eremulidae; Eremulus flagellifer; Taxonomy; 15. Life on land